2020
DOI: 10.1113/ep088927
|View full text |Cite
|
Sign up to set email alerts
|

Insulin‐like growth factor‐binding protein 3 inhibits angiotensin II‐induced aortic smooth muscle cell phenotypic switch and matrix metalloproteinase expression

Abstract: New Findings What is the central question of this study?Insulin‐like growth factor 1 and its major binding protein insulin‐like growth factor binding protein 3 (IGFBP3) are involved in collagen deregulation in several cardiovascular diseases: what is the role of IGFBP3 in thoracic aortic dissection and does it regulate aortic smooth muscle cells’ phenotypic switch? What is the main finding and its importance?IGFBP3 inhibits aortic smooth muscle cells’ phenotypic switch from a contractile to a synthetic phenot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 75 publications
0
5
0
Order By: Relevance
“…Through AT 1 R, AngII stimulation produces changes in the contractile machinery, constisting in decreased expression of contractiles markers such as αSMA (ACTA2), SM22a (TAGLN), and SMMHC (MYH11) (9,46). As others (41,47), in parallel with vascular remodeling, we observed significant changes in contractile markers expression in aortas under AngII infusion, with downregulation of "vascular smooth muscle contraction" pathway, and ACTA2 expression, but also TAGLN and MYH11 (see raw data). In addition, this phenotypic switch was maintained in time despite the end of AngII stimulation, for the "vascular smooth muscle contraction pathway", and also for αSMA expression, both at mRNA and protein levels (Figures 4B, 5A).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Through AT 1 R, AngII stimulation produces changes in the contractile machinery, constisting in decreased expression of contractiles markers such as αSMA (ACTA2), SM22a (TAGLN), and SMMHC (MYH11) (9,46). As others (41,47), in parallel with vascular remodeling, we observed significant changes in contractile markers expression in aortas under AngII infusion, with downregulation of "vascular smooth muscle contraction" pathway, and ACTA2 expression, but also TAGLN and MYH11 (see raw data). In addition, this phenotypic switch was maintained in time despite the end of AngII stimulation, for the "vascular smooth muscle contraction pathway", and also for αSMA expression, both at mRNA and protein levels (Figures 4B, 5A).…”
Section: Discussionmentioning
confidence: 97%
“…Mutations in this gene cause a variety of vascular diseases, such as thoracic dilated aortic disease, coronary artery disease, stroke, and Moyamoya disease (39), and also multisytemic smooth muscle dysfunction syndrome (40). Downregulation of αSMA expression induced by AngII has also been described in vascular SMC in vitro (41,42).…”
Section: Comparative Transcriptomic Profiling Of Angii Vs Angii "Memo...mentioning
confidence: 99%
“…MMPs form a key family of proteolytic enzymes that participate in tissue remodeling by degrading ECM and basement membrane components. Chen et al revealed that MMP9 expression in aortic SMCs can be induced by Ang II and that overexpression of IGFBP3 can reduce the expression of MMP9 [ 40 ]. Suppressing IGFBP3 expression in mice with diabetic cardiomyopathy can alleviate cardiac fibrosis and enhance cell proliferation while inducing AKT and ERK phosphorylation [ 41 ]; this potentially plausible signaling pathway needs to be explored further.…”
Section: Discussionmentioning
confidence: 99%
“…Classically, animal models of Ang II-infusion are the characterized and widely used models of abdominal aortic aneurysms or aortic dissections . In addition, the effect of Ang II on smooth muscle cell phenotypic switching has been demonstrated . Cell proliferation was detected with a cell counting kit-8 (CCK-8, Dojindo, Shanghai, China) after 48 h of culture at 37 °C.…”
Section: Methodsmentioning
confidence: 99%
“…25 In addition, the effect of Ang II on smooth muscle cell phenotypic switching has been demonstrated. 26 Cell proliferation was detected with a cell counting kit-8 (CCK-8, Dojindo, Shanghai, China) after 48 h of culture at 37 °C. Smooth muscle cells were treated with CCK-8 solution with a final concentration of 10% measured at 37 °C for 1−2 h, and then, microplate readers were used to measure absorbance at 450 nm.…”
Section: Preparation and Characterization Of Polymer Micellesmentioning
confidence: 99%